Wood-Based Materials in Building - Mirski, Radosław; Dukarska, Dorota (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This is a reprint of the Special Issue entitled "Wood-Based Materials in Building" and deals with the latest developments in reinforcing construction materials, their joining, glulam-concrete composite beams, the effect of fire-retarding wood on its strength, and the applicability of newly developed wood-based boards and composite insulation materials produced with the use of wood by-products.